From Breeding to Nutrition: Orange‐Fleshed Sweet potatoes in Farming and Food Systems of Uganda, Kenya, and Burkina Faso. - Christinck, Anja; Doka, Marthe Diarra; Horneber, Gottfried; Rugunda, Grace Kagoro; Palé, Grégoire; Whitney, Cory William (The McKnight Foundation, 2016)
The McKnight Foundation commissioned a series of case studies to assess the approach of its Collaborative Crop Research Program (CCRP) as evidenced by the accomplishments and contributions of selected CCRP‐funded projects. The case study presented here focused on three CCRP‐funded projects targeting the breeding, production, and utilization of orange‐fleshed sweetpotatoes (OFSP) in Uganda, Kenya, and Burkina Faso. The projects were interrelated in that the results and practical outcomes of previous projects (e.g., OFSP germplasm and varieties) were used in new ventures and other countries. The case study covers a funding period of twenty years (1994–2014). The objectives were to 1) introduce and describe the background issues and general context, 2) describe the project results, 3) assess CCRP contributions to the projects’ accomplishments, and 4) define program recommendations for current and future CCRP support. A desk review of publications and written documents was used to describe the general context as well as rationales and development of all three projects. Learning, collaboration, and CCRP contributions to the projects’ accomplishments were assessed based on interviews and project reports. Furthermore, focus group discussions, individual interviews, and semi‐quantitative participatory communication tools were applied in Uganda and Burkina Faso to study the project outcomes and impact from the perspectives of actors along the OFSP supply chain. The results comprise the description of the general context (Section 5.1), followed by the presentation of findings for each of the three projects and countries covered (sections 5.2–5.4). Sweetpotato is introduced here as a crop of increasing importance for food and nutrition security, given its relatively high yield per area and its adaptability to poor soil fertility conditions. In Africa, its production area has increased nearly threefold over the last two decades while average yields have remained low. Enhancing resistances to sweetpotato virus disease (SPVD) and insect pests has been a focus of plant breeders working with this crop. Enhancing nutritional quality and meeting the preferences of consumers and food processing industries have also been breeding program objectives. Vitamin A and the issue of Vitamin A deficiency and its effects on human health are briefly introduced. Vitamin A deficiency can severely affect physical and mental development, particularly in young children, including nutritional blindness in extreme cases. It also causes increased morbidity following common infectious diseases. Vitamin A deficiency has thus received increasing attention as a public health issue since the 1990s. Vitamin A is a fat‐soluble vitamin that occurs naturally in animal products such as eggs, milk, meat, and liver. One of its precursors, ß‐carotene, occurs in certain plants and plant products, particularly in orange‐fleshed fruits and dark green leafy or orange vegetables. Examples are squashes, mangoes, carrots, red palm oil, spinach, and other leafy vegetables, as well as OFSP. Approaches to combatting Vitamin A deficiency entail food‐based approaches and supplementation. Biofortification, or purposeful breeding and selection for increased micronutrient contents in staple food crops, is understood as a food‐based approach that targets particularly poor rural populations of developing countries. Biofortification has been successfully applied in several staple crops, one of which is OFSP. Its effectiveness in reducing the incidence of Vitamin A deficiency in vulnerable population groups has been scientifically proven. However, the approach is heavily criticized by some civil society organizations as reducing to a mere technical problem (e.g., breeding sweetpotatoes with higher ß‐carotene content) the root causes of poverty and malnutrition. Dietary diversification has been proposed as an alternative; in practice, various paths are often combined. For example, OFSP is promoted as part of home and school garden projects that aim to enhance nutritional diversity and related knowledge in many African countries. “Nutrition‐sensitive agriculture” is presented as a system approach focusing on nutrition and health of individuals. One important insight gained through this type of research is that there are various interrelated pathways of how changes in farming practices or technologies can influence nutritional outcomes. Agroecological intensification (AEI), on the other hand, aims to make agricultural production more efficient (e.g., with regard to the capacity of production landscapes to provide ecological services or contribute to dietary diversity).The CCRP‐funded sweetpotato project in Burkina Faso targeted the entire OFSP delivery chain. It was based on the introduction of several OFSP varieties via CIP, including some that originated from the breeding work in Uganda. The project activities entailed variety evaluation at several locations and under a range of agroecological conditions. Various agronomic practices were tested, partly in cooperation with farmer groups. Special focus was put on product development and enhancing the content of nutritionally valuable components in processed products (e.g., the contents of ß‐carotene and antioxidants). Project activities included large‐scale awareness campaigns and promotional efforts for OFSP in general. The project could build on the long‐standing experience of one of its partners,bHelen Keller International (HKI) in Burkina Faso, particularly with regard to the promotion of nutritional and health related knowledge and issues. In this project, cross‐institutional learning and cooperation appear to have taken place in spite of the reported challenges and the time demanded for coordination. Participating researchers stated that together they achieved more and in less time than they would have be able to do on their own. An identified weakness was the informal involvement of farmers, their roles and responsibilities insufficiently clarified. The production and marketing of sweetpotato roots remain a challenge because of risks involved at various nodes of the delivery chain; however, in the focus region, OFSP was generally accepted by many people and grown by farmers, at least on small plots, to meet their families’ requirements. In Chapter 6, the results are discussed in relation to the projects’ contributions to breeding progress achieved in sweetpotato, their potential to address Vitamin A deficiency, their ways of addressing linkages between agriculture and nutrition, and the project design. Lessons learned (Chapter 7) addresses major problem areas for developing OFSP supply chains, one being the high seed cost in relation to the product value and risks involved in OFSP production and marketing. Value‐chain development and improved nutritional outcomes for vulnerable groups through promotion of self‐consumption are presented as potentially conflicting goals. Issues such as resource endowment for different groups of actors to ensure that they can benefit from such approaches require consideration. Seed system development for OFSP planting material involves several challenges, particularly the need for developing adequate infrastructure for multiplication, quality control, and marketing of vines. The present distribution system depends heavily on the priorities of external actors (e.g., NGOs and their respective donors). Long‐term funding of projects can effectively help reach impact at larger scales. Assimilating expertise on the implementation of participatory multi‐actor projects involving 4 non‐academic partners could help make the project activities more relevant to farmers and their market partners. Lastly, system perspectives and gender aspects could be better integrated in future projects. Our main recommendations with regard to future CCRP funding strategies are to: • Continue long‐term funding and nonmonetary support to maximize impacts; • Invest more time and resources in a project pre‐phase to ensure that all partners needed to achieve the desired change are identified and, whenever possible, formally linked to the project and its management structures; • Consider full budget funding in order to ensure that the projects ‘quality and impact are not limited by a lack of resources; • Consider professional project coordination in order to relieve scientists from this task, particularly in the case of larger projects involving multiple actors; • Achieve more clarity on the resources required by each partner to participate in the research; • Place greater emphasis on the integration of diverse knowledge and co‐innovation of solutions to the problem or issue addressed; • Better address influencing macro factors to facilitate impact at larger scales; • Make a gender perspective mandatory for all future projects (e.g., by assessing its relevance for all project objectives, activities, and outcomes when establishing the proposal and throughout the project ‘s lifetime). Some of the above recommendations are already practiced in current CCRP funding strategies.
Keywords: orange‐fleshed sweetpotatoes; Nutrition; Uganda; Kenya; Burkina Faso